An exploration of public participation in policy making amongst Cape Town civic organisations - Patsika, Dahlia Zvikomborero (Department of Social Development, 2022)
This study explored the role played by civic organisations in policy formulation through public participation. A qualitative research design was used in which two sample sets were purposively selected to participate in the study. The first sample set comprised of general members of civic organisations, while the second comprised of stakeholders in the community such as members of the business community, nongovernmental organisations, and the municipal council. In-depth interviews were conducted and facilitated through a semi-structured interview guide. The interviews were guided by the overall aim and objectives of the study which included exploration of participants' perceptions regarding the following: their understanding of public participation, different forms of public participation, roles of civic organisations in policy making, influence of public participation in decision-making at local level, ways in which public participation can be improved at local level; and public participation in the context of the Covid-19 pandemic. The study found that civic organisations' roles were indispensable in policy formulation as they facilitate meaningful public engagement with local government structures, legislatures, and key stakeholders in their communities in the context of policy making. Further, civic organisations enhance democracy through holding local authorities and policy-makers accountable for their actions in development. The findings also show that public participation is a fundamental and inclusive process for citizens in decision-making processes, whether directly as interest groups or individuals, or indirectly through their elected representatives. Participants from civic organisations perceived different forms of public participation as voting, public meetings, and petitions. However, key informants highlighted that most public participation practices were ‘tick-box' exercises because they did not facilitate meaningful participation for citizens. Finally, the study found that the outbreak of the Covid-19 pandemic severely affected public participation processes. Because many civic organisations' activities had to stop, service delivery in some communities was affected. The study's major recommendation is that local government authorities such as ward councilors and municipal managers should aim to facilitate collaborative governance with civic organisations and citizens. This could be done through forming meaningful partnerships between civic organisations, stakeholders, and the local government. The study argues that this will ensure working towards an Integrated Development Plan and a people-centered approach to development in policy making.